Mosaic partial trisomy 17q2. Issue 9 (September 1991) - King, P A; Ghosh, A; Tang, M
Abstract : Examination of an infant born after prenatal diagnosis of mosaic partial trisomy 17q2 showed the unique phenotypic features of this chromosomal abnormality, that is, frontal bossing, large mouth, brachyrhizomelia, and hexadactyly. Amniocentesis was performed because of polyhydramnios and ultrasound diagnosis of fetal craniofacial dysmorphology and rhizomelic shortening of the limbs. Chromosomal mosaicism was restricted to fetal tissue and amniotic fluid cells. The placental chromosomal complement was normal, suggesting that the abnormality developed after differentiation of embryonic and trophoblastic cells. This emphasises the usefulness of cytogenetic evaluation of placental, fetal, and amniotic fluid cells in delineating the pathogenesis of congenital abnormalities.